Displacement of a DNA binding protein by Dda helicase - Byrd, Alicia K. (Oxford University Press, 2006)
Bacteriophage T4 Dda helicase has recently been shown to be active as a monomer for unwinding of short duplex oligonucleotides and for displacing streptavidin from 3′-biotinylated oligonucleotides. However, its activity for streptavidin displacement and DNA unwinding has been shown to increase as the number of Dda molecules bound to the substrate molecule increases. A substrate was designed to address the ability of Dda to displace DNA binding proteins. A DNA binding site for the Escherichia coli trp repressor was introduced into an oligonucleotide substrate for Dda helicase containing single-stranded overhang. Here we show that a Dda monomer is insufficient to displace the E.coli trp repressor from dsDNA under single turnover conditions, although the substrate is unwound and the repressor displaced when the single-stranded overhang is long enough to accommodate two Dda molecules. The quantity of product formed increases when the substrate is able to accommodate more than two Dda molecules. These results indicate that multiple Dda molecules act to displace DNA binding proteins in a manner that correlates with the DNA unwinding activity and streptavidin displacement activity. We suggest a cooperative inchworm model to describe the activities of Dda helicase.